Influence of cutting parameters and plasma cutting mode on cutting quality and process noise - Kolarikova, Marie; Kolarik, Ladislav; Panacek, Tomas; Kralicek, Jan; Kucera, Miroslav; Gurcik, Tomas (Manufacturing Technology Journal, 2020)
Plasma cutting is an ever-evolving method of industrial cutting of materials. Like all modern methods, it must meet the requirements for the quality of the cut, but also the hygiene and safety regulations set by European legislation. New ways are being sought to reduce process noise while improving the quality of the cutting surface. The article aims to compare two cutting modes (Contour Cut and Silent Cut) in terms of both the quality of the cut (roughness of the cutting surface, size of the heat affected area, perpendicularity and bevel angle of the cutting surface) and in terms of noise of the cutting pro-cess. The results in the article clearly show that the use of the Silent Cut mode has a demonstrably positive effect on the level of noise produced but also on the quality of the cut.
Keywords: Plasma Cutting; Cutting Quality; Noise; Roughness of the Cutting Surface; Hardness